Debatable discourse of phraseology: manipulations and linguistic games - Koženiauskienė, Regina (Lietuvių kalba, 2008)
The paper discusses a debatable discourse of phraseology, both written and spoken, and analyses texts of different genres of public discourse. More attention is devoted to the semantic structure of idiomatic expressions and their modifications, i.e. their occasional usage, their shift from indirect to direct meanings, from fixed to free word combinations (co-occurrences) and vice versa. The paper treats the above modifications as a linguistic game: non-standard, at first sight even illogical, usage aimed at hindering the understanding rather than transmitting information, as pointed out by language experts. This might be due to several reasons: to attract the attention of the readership or the audience, to circumvent the law (like in alcohol advertisements) or to avoid being treated as an offender by expressing one's negative attitude to another person. A linguistic game offers numerous opportunities to manipulate, so does linguistic meaning in its numerous extensions and with no obvious boundaries between distinct senses. Occasional idiomatic expressions, insulting taboos and idioms with non-standard implications are well-marked and often require linguistic expertise; however, due to the underlying linguistic game, they cannot be always disputed as regular conclusions. If nonetheless linguistic expertise is sought, it is considered valuable. Still it remains only one of possible stylistic interpretations of a debatable text.
Keywords: none